Menelusuri Jejak Marginalisasi Anak Disleksia dalam Pendidikan Islam - Afif Syaiful Mahmudin; Weni Tria Anugrah Putri; Muhammad Heriyudanta (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study begins with observations of dyslexic children who are often underestimated in the academic field. This study aims to explain the process of marginalization of children with dyslexia. This is part of the literature study (Library Research). There are two types of data sources in this study, the first cases of teacher treatment of dyslexic children that appear in real life and second qualitative data sourced from documents such as reference books. The results of the analysis in this study indicate that marginalization occurs because of the lack of support from parties around the child, causing the child's achievement to decline. Minder is one of the effects of this. Willingness to communicate with his friends was reduced. He continued, his peers lacked enthusiasm in socializing with these children. Opportunities to do things like other students will decrease and feel marginalized